Loret’s Marketing Revolution: Audience Representation as Positioning Strategy in Seventeenth‑Century Newspapers - Schuwey, Christophe (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2021)
The inception of Jean Loret’s Lettre en vers in 1652 constituted a major evolution in information culture. Borrowing the concepts of positioning and segmentation from marketing studies, this article insists on Loret’s tour de force: by portraying Marie de Nemours as the reader and recipient of the news, he conferred the veneer of a private and handwritten correspondence to an object that was public and sold. This formula, which I describe as “addressed information,” presented multiple advantages: it created a new, affective, intimate, and agentive relationship between the readers and the information, renewed audience segmentation, and distinguished the Lettre en vers from the competing gazettes of the time. The article also studies Loret’s depictions of a wider audience and demonstrates the later success of his formula in France, especially in the case of the Mercure galant.